Scaling up integration: development and results of a participatory assessment of HIV/TB services, South Africa - Caldwell Judy; Azevedo Virginia; Chopra Mickey; Scott Vera; Naidoo Pren; Smuts Brenda (BMC, 2010)
Abstract Background In South Africa the need to integrate HIV, TB and STI programmes has been recognised at a policy and organisation level; the challenge is now one of translating policies into relevant actions and monitoring implementation to ensure that the anticipated benefits of integration are achieved. In this research, set in public primary care services in Cape Town, South Africa, we set out to determine how middle level managers could be empowered to monitor the implementation of an effective, integrated HIV/TB/STI service. Methods A team of managers and researchers designed an evaluation tool to measure implementation of key components of an integrated HIV/TB/STI package with a focus on integration. They used a comprehensive health systems framework based on conditions for programme effectiveness and then identified and collected tracer indicators. The tool was extensively piloted in two rounds involving 49 clinics in 2003 and 2004 to identify data necessary for effective facility-level management. A subsequent evaluation of 16 clinics (2 per health sub district, 12% of all public primary care facilities) was done in February 2006. Results 16 clinics were reviewed and 635 records sampled. Client access to HIV/TB/STI programmes was limited in that 50% of facilities routinely deferred clients. Whilst the physical infrastructure and staff were available, there was problem with capacity in that there was insufficient staff training (for example, only 40% of clinical staff trained in HIV care). Weaknesses were identified in quality of care (for example, only 57% of HIV clients were staged in accordance with protocols) and continuity of care (for example, only 24% of VCT clients diagnosed with HIV were followed up for medical assessment). Facility and programme managers felt that the evaluation tool generated information that was useful to manage the programmes at facility and district level. On the basis of the results facility managers drew up action plans to address three areas of weakness within their own facility. Conclusions This use of the tool which is designed to empower programme and facility managers demonstrates how engaging middle managers is crucial in translating policies into relevant actions.